Factors associated with psychiatric admission and subsequent self-harm repetition: a cohort study of high-risk hospital-presenting self-harm. (2nd November 2021) - Cully, Grace; Corcoran, Paul; Leahy, Dorothy; Cassidy, Eugene; Steeg, Sarah; Griffin, Eve; Shiely, Frances; Arensman, Ella
Abstract: Background: Individuals presenting to hospital with self-harm of high lethality or high suicidal intent are at high risk of subsequent suicide. Aim: To examine factors associated with psychiatric admission and self-harm repetition following high-risk self-harm (HRSH). Method: A cohort study of 324 consecutive HRSH patients was conducted across three urban hospitals (December 2014–February 2018). Information on self-harm repetition was extracted from the National Self-harm Registry Ireland. Logistic regression models examined predictors of psychiatric admission and self-harm repetition. Propensity score (PS) methods were used to address confounding. Results: Forty percent of the cohort were admitted to a psychiatric inpatient setting. Factors associated with admission were living alone, depression, previous psychiatric admission, suicide note and uncommon self-harm methods. History of emotional, physical or sexual abuse was associated with not being admitted. Twelve-month self-harm repetition occurred in 17.3% of cases. Following inverse probability weighting according to the PS, psychiatric admission following HRSH was not associated with repetition. Predictors of repetition were recent self-harm history, young age (18–24 years) and previous psychiatric admission. Conclusion(s): Findings indicate that psychiatric admission following HRSH is not associated with repeated self-harm and reaffirms the consistent finding that history of self-harm and psychiatric treatment are strong predictors of repetition.